Infectious serology, how to test large series without pooling samples - Bennaoum, Mohammed Nazim; Adda, Affaf; Chekkal, Mohamed; Seghier, Fatima (Journal of Ideas in Health, 2020)
Pooling samples for serological testing was used first during the second world war. It was described later as a cost-effective technique permitting large screening of populations, especially for new infectious diseases. However, the dilution effect is responsible for decreasing sensitivity, limiting its use in practice, especially in blood banking. In this paper, we describe a modification of the classic enzyme-linked immunosorbent assay (ELISA) procedure, which permits the test of indefinite samples using just one well. Specimens are tested pure one by one without any dilution, so sensitivity remains unchanged. This new procedure is time-consuming but can be considered as a revolution in qualitative ELISA testing.